On the Logical Progression of the Morality of Anti-Dühring - Yuan, Ziqiong; Liu, Zehua (International Journal of Social Sciences and Public Administration, 2024)
The Anti-Dühring Theses is Engels’ most powerful exposition of the concept of morality. In this work, Engels put the concept of equality based on materialistic view of history with extremely pungent strokes, used scientific criticism as a weapon to counter Dühring’s concept of equality, and took "elimination of classes" as the logical destination of the proletariat, thus forming the logical progression of the idea of equality, which constitutes the basic content of the Marxist concept of equality.